Response of renal cell carcinoma to ibrutinib, a bruton tyrosine kinase inhibitor, in a patient treated for chronic lymphocytic leukemia - Hosier, Gregory W.; Touma, Naji J. (Canadian Urological Association Journal, 2017)
Ibrutinib is a bruton tyrosine kinase (BTK) inhibitor approved for B cell malignancies. Although there are currently two clinical trials evaluating ibrutinib in combination with nivolumab (programmed cell death protein 1, PD-1, inhibitor) or everolimus (mammalian target of rapamycin, mTOR, inhibitor) for metastatic renal cell carcinoma (RCC), there are no reports of RCC (metastatic or non-metastatic) showing response to a BTK inhibitor in humans. Here we report a 22-month clinical response of biopsy-proven RCC to ibrutinib. This is unexpected, given that BTK is not wellimplicated in RCC pathophysiology. We explore a possible mechanism for the response of RCC to ibrutinib through inhibition of interleukin-2-inducible T-cell kinase (ITK) leading to enhanced antitumour immune responses.